Case report: A novel mutation in RTEL1 gene in dyskeratosis congenita - Nisar, Haider; Khan, Memoona; Chaudhry, Qamar Un Nisa; Iftikhar, Raheel; Ghafoor, Tariq (Frontiers in Oncology, 2023)
Dyskeratosis congenita (DKC), also known as Zinsser–Cole–Engman syndrome, is a telomeropathy typically presenting as a triad of leukoplakia, nail dystrophy, and reticular hyperpigmentation. Reported genetic mutations linked to DKC include DKC1, TINF2, TERC, TERT, C16orf57, NOLA2, NOLA3, WRAP53/TCAB1, and RTEL1. Homozygous, compound heterozygous, and heterozygous mutations in RTEL1 (RTEL1, regulator of telomere elongation helicase 1) gene on chromosome 20q13 are known to cause autosomal dominant as well as recessive DKC. Pathogenic variants of RTEL1 gene in DKC patients include c.2288G>T (p. Gly763Val), c.3791G>A (p. Arg1264His), and RTEL p. Arg981Trp. We report a novel homozygous variant of RTEL1, transcript ID: ENST00000360203.11, exon 24, c.2060C>T (p.Ala687Val), in a patient of DKC presenting with leukoplakia, dystrophic nails, reticulate pigmentation, and positive family history of a similar phenotype. The novel variant, reported as a variant of uncertain significance, may therefore be considered diagnostic for DKC in a Pakistani population.